Structuring information from unstructured textual document - Ling, Chei Huang. (Universiti Malaysia Sarawak (UNIMAS), 2008)
This paper presents an approach for structuring information. Structuring information means to convert a textual document into a simple structured information representation such as graphical map. As more and more documents are generated everyday, the structured information is useful to enable users easily grasp the ideas of a document without reading the document word by word. The application for structuring information from the unstructured textual document is developed by using the General Architecture for Text Engineering (GATE) tool, which is developed by University of Sheffield, United Kingdom. The implementation of this application enables the users to get the structured information of a document quickly. The application first read an unstructured textual document, such as a paragraph of text. Then the document's main points will be extracted. Finally, the main points will be illustrated in graphical map, which is simple and easy to understand. The graphical map represents the structured information from the document.